Recurrent mutations associated with isolation and passage of SARS coronavirus in cells from non‐human primates - Poon, Leo L.M. (J Med Virol, 2005)
Four clinical isolates of SARS coronavirus were serially passaged in two primate cell lines (FRhK4 and Vero E6). Viral genetic sequences encoding for structural proteins and open reading frames 6–8 were determined in the original clinical specimen, the initial virus isolate (passage 0) and at passages 5, 10, and 15. After 15 passages, a total of 15 different mutations were identified and 12 of them were non‐synonymous mutations. Seven of these mutations were recurrent mutation and all located at the spike, membrane, and Orf 8a protein encoding sequences. Mutations in the membrane protein and a deletion in ORF 6–8 were already observed in passage 0, suggesting these amino acid substitutions are important in the adaptation of the virus isolate in primate cell culture. A mutation in the spike gene (residue 24079) appeared to be unique to adaptation in FRhK4 cells. It is important to be aware of cell culture associated mutations when interpreting data on molecular evolution of SARS coronavirus. J. Med. Virol. 76:435–440, 2005. © 2005 Wiley‐Liss, Inc.